On an OptLearn implementation using collaborative filtering. - Fuster López, Alejandro; Guerrero-García, Pablo; Hendrix, Eligius María Theodorus; Martínez-Cruz, Jesús; Nowak, Ivo (My University, 2023)
The aim of the iMath project is to develop a recommender system where a student is recommended a next question or literature in a learning platform MathE. This paper describes the systems developed based on collaborative filtering python application Surprise by the partners of the project based in Universidad de Málaga and Hamburg. Moreover, it describes further development towards hybridization of recommenders and the inclusion of concept maps.
Keywords: Matemáticas - Estudio y enseñanza - Innovaciones tecnológicas; Enseñanza asistida por ordenador; E-learning; Collaborative filtering; Recommender system; Mathematics